Optimal solution to cybercrimes lessons from law and economics - Majuca, Ruperto P. (2014)
A model is presented wherein cybercrimes are addressed through a combination of private and public measures. This captures the substitutability of private and public responses and determines the optimal combination of these approaches. The socially optimal level of security is achieved by equalizing the marginal-benefit-to-marginal-cost ratios of each of the three alternatives: private security investment, nonrivalrous security investment, and law enforcement measures. The interrelatedness of Internet risks causes individual firms to underinvest in private and public security goods. The government thus lowers the level of police enforcement expenditures to induce firms to invest more in individual precautions. In certain conditions, cooperation results in socially optimal levels of expenditures in private and public security goods. The Shapley [1953] value can be used as a criterion for allocating the costs and benefits among the members of a security cooperative.
Keywords: Computer crimes